1975
DOI: 10.1111/j.1751-1097.1975.tb06656.x
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Microsecond Delayed Light Emission From Scenedesmus Obuquus at Intermittent Illumination

Abstract: Abstract— For dark adapted cells, the intensity of delayed light at the onset of a light period depends on the length of the preceding dark period. Under our experimental conditions, the exciting laser light seems to reduce the intermediate pool located between the two photosystems. If dark adapted cells are illuminated, mechanisms are established within about 20 s which appear to drain electrons from the intermediate pool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A major aspect of these experiments is the dependence of delayed fluorescence emission after a single flash upon preillumination of the sample (induction effects) (Ruby, 1971). A number of other investigators have examined the behavior of induction effects in delayed fluorescence in plants; among them Mar et al (1975), Strehler and Lynch (1957), Kessler, Arthur and Strehler (1957), Bruegger and Franck (1958) Clayton (1965), Itoh et al (1971, Lavorel (1975) and Holzapfel and Haug (1975). Mar et al showed in their investigation that induction curves of delayed fluorescence obtained with a phosphoroscope can lead to erroneous conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…A major aspect of these experiments is the dependence of delayed fluorescence emission after a single flash upon preillumination of the sample (induction effects) (Ruby, 1971). A number of other investigators have examined the behavior of induction effects in delayed fluorescence in plants; among them Mar et al (1975), Strehler and Lynch (1957), Kessler, Arthur and Strehler (1957), Bruegger and Franck (1958) Clayton (1965), Itoh et al (1971, Lavorel (1975) and Holzapfel and Haug (1975). Mar et al showed in their investigation that induction curves of delayed fluorescence obtained with a phosphoroscope can lead to erroneous conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that this effect is a minor contribution, a fraction of the dark count in magnitude, and can be ignored for our measurements. Nevertheless, we suggest avoiding the oversaturation limits by incorporating a neutral density filter and scaling the intensity of the excitation LED so that delayed fluorescence kinetics can interrogate timescales of microseconds to minutes [ 50 ]. For the purposes of delayed fluorescence experiments here, the temporal limit of detection was more than adequate, and the incorporation of the neutral density filter was deemed unnecessary.…”
Section: Discussionmentioning
confidence: 99%